Patient Satisfaction and Compliance in One-Day Care Chemotherapy: A Study at Dr. Moewardi Hospital - Hadi, Cahyono; Isa, Muzakar; Sutrisna, Em; Pangestu, Mulyoto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2025)
The purpose of this study is to ascertain how satisfied and compliant cancer patients are with Dr. Moewardi Hospital's one-day care chemotherapy treatments, as well as how these factors relate to age, gender, education, and cancer type. Methods of research: This study used a descriptive method with a quantitative approach and correlational design. One hundred individuals who satisfied the inclusion and exclusion criteria made up the study's sample. A questionnaire was employed as the data collection method. According to the study's findings, 53% of chemotherapy patients were very satisfied, 37% were satisfied, and 10% were fairly satisfied when the five primary quality characteristics of tangibles, responsiveness, assurance, empathy, and reliability, were used to gauge their degree of satisfaction. 99% of cancer patients have complied with one-day care chemotherapy services. There is a noteworthy and favorable correlation between cancer patients' satisfaction and compliance with one-day care chemotherapy services. The main findings in this study indicate that most one-day care chemotherapy patients at Dr. Moewardi Hospital were very satisfied with the services provided, with a satisfaction level reaching 53%, and 99% of patients showed high compliance with the chemotherapy schedule. In addition, a significant and positive relationship was found between the level of satisfaction and patient compliance. Based on these findings, recommendations for further research are to explore non-demographic factors, such as socioeconomic status and family support, which may affect patient satisfaction and compliance, as well as to expand the study sample to obtain more comprehensive results.